Expression of elongation factor-2 kinase contributes to anoikis resistance and invasion of human glioma cells - Zhang Li; Zhang Yi; Liu Xiao-yuan; Qin Zheng-hong; Yang Jin-ming (Acta Pharmacologica Sinica; Vol 32, No 3 (March 2011): Acta Pharmacologica Sinica, 2016)
Aim: To determine whether elongation factor-2 kinase (eEF-2 kinase) contributes to the malignant phenotype of glioblastoma multiforme by promoting the migration and invasion of glioma cells. The mechanism involved was also explored. Methods: Human glioma cell lines T98G and LN-229 were used. The expression of eEF-2 kinase was silenced using siRNA, and the invasive potential of tumor cells was assessed using a wound-healing assay and a Matrigel invasion assay. Apoptosis was determined using propidium iodide (PI) staining and Western blot analysis of cleaved caspase-3. Results: Silencing the expression of eEF-2 kinase by siRNA significantly suppressed both the migration and invasion of human glioma cells. Silencing eEF-2 kinase expression also sensitized glioma cells to anoikis, thereby decreasing tumor cell viability in the absence of attachment. Treatment of tumor cells with the caspase inhibitor z-VAD-fmk down-regulated Bim accumulation and abolished glioma cell sensitivity to anoikis. Conclusion: The results suggest that the expression of eEF-2 kinase contributes to migration and invasion of human glioma cells by protecting them from anoikis. eEF-2 kinase expression may serve as a prognostic marker and a novel target for cancer therapy.